A Study on Problems of Women Entrepreneurs in Urban Area with Special Reference to Thiruvananthapuram in Kerala - J. Shyla; S. Natrajan; Hari Priya; Jeethu James; Ancy Varghese; Shiny Vijayan and Aliber Marshel 3 (Journal of Research in Business and Management, 2014)
The principle purpose of this study is to identify the major problems faced by women entrepreneurs in Thiruvananthapuram and also find the impact of these problems on the working efficiency of these women entrepreneurs. Research aim/method: The data collected was subjected to quantitative analysis Total, Average and Percentage/frequency to find the major problematic factors and test is applied to find the statistical significance through the respondents demographic variable statistical percentage analysis of the hypotheses for possible acceptance or rejection is used in the study. Result: Results of the analysis indicated that women entrepreneurs in Thiruvananthapuram District generally countenance on three kinds of problems like entrepreneurial/business problems, social/personal and financial problems too. And all these three types of problems initial two criteria have negative relation but third one was positive relation with the working efficiency of women entrepreneurs. Realistic inference: This study might be help the government regulators in addressing the problems of women entrepreneurs in Kerala to take an actions towards the developing their performance and in turn to promote the paucity of women‘s welfare from the Kerala district of Thiruvananthapuram. Innovation/assessment: This research article adds to the literature on the determinants of problems faced by the women entrepreneurs in Thiruvananthapuram In particular, it is the first study of its own type in case of Thiruvananthapuram District which has been categorized the problems faced by the women entrepreneurs in entrepreneurial/business problems, social/personal tribulations and nominal problems as well as financial crisis too. According to the study it has been observed that Women are very good capitalist, and prefer to desire the identical while they can sustain occupation for life balance. Even though we have many successful Women Entrepreneurs in our country, but as we have a male dominated culture there are many challenges which women entrepreneurs face such a kind of challenges and discrimination from the family and Society.